Update of Immunomodulatory Therapy for Inflammatory Bowel Disease - Charles N Bernstein (Canadian Journal of Gastroenterology)
For several decades corticosteroids were the only potent immunomodulatory agents effective and available for active inflammatory bowel disease (IBD). The past decade ha seen an enhanced knowledge of the immune response in lBD and a better understanding of how common immunomodulatory agents work. Furthermore, more specific mediators of the abnormal immune response have been identified, so that therapy can be more targeted. Purine analogues have proven efficacy in achieving and maintaining remission in both Crohn’s disease and ulcerative colitis. Methotrexate has proven efficacy in active Crohn’s disease. Both of these classes of drugs requires weeks to months of treatment before any benefit is seen. Intravenous cyclosporine is efficacious in acute severe ulcerative colitis and can settle active disease within days of administration. It is unclear whether oral cyclosporine offers any advantage at maintaining remission, once achieved. Oral cyclosporine in Crohn’s disease has been proven to be ineffective at either achieving or maintaining remission; however, intravenous cyclosporine in Crohn’s disease has not been rigorously tested. Newer immunomodulatory agents have been designed for specific targets. and in particular monoclonal antibodies that block the effects of interleukin-1, tumour necrosis factor-alpha and the T cell receptor are available for clinical trials. We are in an era of expanding therapeutic approaches to these diseases, including the refined use of readily available agent, the development of newer, more targeted agents and a broader understanding of how agents may be effectively used simultaneously or sequentially.